Uptake of nutrients by BR 22 rice plants at two growth stages driven by locally made organic amendments - Mia, Md Harun; Sikder, Md Raisuddin; Saha , Mithun Kumar; Khan, Md Harunor Rashid (Dhaka University Journal of Biological Sciences, 2025)
An on-site experiment was done at the Aman season to evaluate the potential differences in nutrient supply by five different organic amendments (OAs) to BR 22 rice following a completely randomized block design (CRBD). The OAs were incorporated in the subplots at 0, 5, and 10 t ha-1. The amendments were observed to have varied significantly (p < 0.05) in supplying the mineral nutrition of rice plants both in the maximum tillering and harvesting stages. With respect to N and P, the treatment of rice straw plus cow dung compost of 1:4 at its higher dose (T5) was found to have the most potential to enhance these nutrients accumulation in shoots at the maximum tillering stage at 21.05 and 7.0 g kg-1 N and P, respectively. Whereas, TC (T9) was detected with the highest K contents (39.95 g kg-1) in shoots at the tillering stage followed by RH (T13) and SD compost (T11). As per the secondary nutrients, TC (T9) manifested the highest S, compost mixture (T5) for Ca, and treatment (T13) accounted for the highest Mg uptake in the rice plant. Moreover, the findings showed that OAs significantly augmented the contents of micronutrients Zn, Fe, and Mn in rice plants over the control. In most instances, the nutrient content declined as the plants turned towards maturity. Dhaka Univ. J. Biol. Sci. 34(2): 71-88, 2025 (July)